2022
DOI: 10.1021/acs.jpcc.2c01978
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Simulation of the ESR Spectrum─Sensitive Tool to Identify the Local Environment of Asphaltenes In Situ

Abstract: An original method to study the local environment of vanadyl-containing components of heavy oils based on finetuning simulation of their electron spin resonance (ESR) spectra in situ is developed. The approach is backgrounded on precise computation of anisotropic ESR spectra of individual porphyrin complexes in specific solvents modeling a particular local environment of certain polarity using specific g and A tensor components, their dispersion, and linewidth determined by unresolved super-hyperfine interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…The experimental data for individual solvents clearly demonstrate that the axial structure of the VOOEP spin probe makes it possible to follow the polarity changes in the axial environment of vanadyl due to weak polar bonds formed at low temperatures in polar solvents. 49,65 S3. Similar to polar solvents, in the V-oil-W sample, an increase in the A iso parameter by 9.9 MHz is observed when the temperature changes from 130 to 400 K, which indicates the coordination of most of the VOOEP molecules to the polar fragments of the oil components when the solution is frozen.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental data for individual solvents clearly demonstrate that the axial structure of the VOOEP spin probe makes it possible to follow the polarity changes in the axial environment of vanadyl due to weak polar bonds formed at low temperatures in polar solvents. 49,65 S3. Similar to polar solvents, in the V-oil-W sample, an increase in the A iso parameter by 9.9 MHz is observed when the temperature changes from 130 to 400 K, which indicates the coordination of most of the VOOEP molecules to the polar fragments of the oil components when the solution is frozen.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Currently, a number of methods are being developed that allow obtaining information about the structure, dynamics, and local environment of heavy components in oils at the atomic and molecular level, among which spectroscopic (FTIR spectroscopy, ,, small-angle scattering (SAS), and dynamic light scattering (DLS)) , and resonance (NMR and electron spin resonance (ESR)) , methods can be distinguished. Each of these methods has advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of longitudinal relaxation times, T 1 , in model samples showed that the wax concentration has virtually no effect on T 1 . This is likely due to the lack of active paramagnetic centers in model wax solution such as the VO 2+ (vanadyl) fragment of asphaltenes 63 or highly dispersed rock particles, both abundantly presented in the natural oils. Nevertheless, the relatively large molecular size of long-chain paraffins favors the slow reorientation (tumbling) motion, which give rise to quite long T 1 values due to the modulation of correlation times, τ c , of the fluctuating local magnetic fields responsible for the dipole−dipole mechanism of NMR relaxation (according to the Bloembergen−Purcell−Pound theory, 64 the T 1 reaches the minimum at ω 0 τ c ∼ 1).…”
Section: Nmr Signal Attenuation Decays Of Wax Solutionmentioning
confidence: 99%
“…The low-intensity signal components are difficult to analyze through standard spectral simulations in a variety of cases [17][18][19]. Accurate spectral analysis in such cases require quantum chemical computations or special techniques [20][21][22], but without sufficient expertise and knowledge in the field, the interpretations rely heavily on the researchers' experience and intuition than the robustness of the method. An even more challenging problem, which occurs frequently, is the presence of more than one structurally similar molecules in a system.…”
Section: Introductionmentioning
confidence: 99%